2016
DOI: 10.12659/pjr.895701
|View full text |Cite
|
Sign up to set email alerts
|

Gd-EOB-DTPA-Enhanced MR Imaging of the Liver: The Effect on T2 Relaxation Times and Apparent Diffusion Coefficient (ADC)

Abstract: SummaryBackgroundTo investigate the effect of gadoxetic acid disodium (Gd-EOB-DTPA) on T2 relaxation times and apparent diffusion coefficient (ADC) values of the liver and focal liver lesions on a 1.5-T system.Material/MethodsMagnetic resonance (MR) studies of 50 patients with 35 liver lesions were retrospectively analyzed. All examinations were performed at 1.5T and included T2-weighted turbo spin-echo (TSE) and diffusion-weighted (DW) images acquired before and after intravenous administration of Gd-EOB-DTPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus, DKI might also be beneficial in the differentiation and classification of focal liver lesions based on their structural complexity. Even though recent studies showed that DWI can be acquired before or after contrast media injection with no relevant effect on quantitative ADC values (19), we chose to analyze both groups separately. This was done as the influence of contrast agent administration on DKI values in this setting is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DKI might also be beneficial in the differentiation and classification of focal liver lesions based on their structural complexity. Even though recent studies showed that DWI can be acquired before or after contrast media injection with no relevant effect on quantitative ADC values (19), we chose to analyze both groups separately. This was done as the influence of contrast agent administration on DKI values in this setting is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous reports that only discussed one single ADC value, this study evaluated the ADCs at four b-values (50, 800, 1,000, and 1,200 s/mm 2 ), and found no difference between the ADCs before and after enhancement, indicating that the ADC values of focal hepatic lesions would not be affected by Gd-EOB-DTPA, regardless of whether this was a high b-value or low b-value DWI. However, unlike hepatic lesions, the post-contrast ADC values of normal hepatic parenchyma were significantly lower than those pre-contrast, which was speculated to be related to the uptake of Gd-EOB-DTPA by normal liver tissue (5)(6)(7).…”
Section: Discussionmentioning
confidence: 92%
“…Several strategies have been used to overcome this problem, including shortening the delay time of the HBP (4) and optimizing the scanning of the magnetic resonance (MR) protocol (5)(6)(7)(8)(9). Of these, the adjustment of the diffusion weighted imaging (DWI) sequence scanning order from pre-contrast to post-contrast is feasible and crucial.…”
mentioning
confidence: 99%
“…Ab-MRI protocols should enable a reduction in imaging acquisition time, as noted by Canellas et al [ 12 ], who reported that Ab-MRI protocols may be performed in less than 15 min, while standard liver MRI takes up to 30 min. The implementation of Ab-MRI protocols can be expected because they have shown no significant influence on gadoxetic acid administration on T2-weighted imaging and diffusion sequences in regard to acquisition and image interpretation[ 29 , 30 ], suggesting that patients could undergo contrast administration without a bolus injection before entering the MRI suite. This would not only reduce the imaging acquisition time, but also provide several other advantages.…”
Section: Discussionmentioning
confidence: 99%